Third Conference on Blue Collar Workers and Their Communities: Windsor, April 1979 - Storey, Robert (Labour / Le Travail, 1980)
Assesses the Windsor conference versus the London meeting of the previous year, as well as the meaning of the Windsor conference for blue-collar workers. Concludes that the Windsor conference, with its sessions on industrial conflict and on the past and futue of the Canadian working class, was more firey; and that academic work, including theory, must also be relevant and accessible to workers and their struggles.